Faktor-Faktor yang Mempengaruhi Minat Berinvestasi Generasi Z: Studi pada Mahasiswa Universitas Budi Luhur - Nabila Tri Alfiani; Retno Fuji Oktaviani (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The phenomenon of increased investment participation among Generation Z amidst digital convenience needs to be balanced with adequate financial literacy. This study aims to analyze the effect of investment knowledge, investment capital, investment motivation, and risk perception on students' investment interest. A quantitative approach with an explanatory survey design was applied to a population of 1,017 Universitas Budi Luhur students. A sample of 100 respondents was selected using purposive sampling. Primary data was collected through Likert scale questionnaires and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results show that investment knowledge, investment capital, and investment motivation have a positive and significant effect on investment interest, while risk perception has no significant effect. In conclusion, improving investment literacy and affordable capital access is crucial to encourage investment interest. Therefore, active involvement from educational institutions and financial service providers is needed to design effective investment educational programs.